Analisis Pemetaan Dan Pemeliharaan Infrastruktur Jaringan Distribusi Gardu Menggunakan MapSource pada PT PLN (Persero) UP3 Lubuk Pakam - Muhammad Anwar (Jurnal Pendidikan Sains dan Teknologi Terapan | E-ISSN : 3031-7983, 2026)
The development of information technology encourages PT PLN (Persero) UP3 Lubuk Pakam to improve efficiency in dynamic mapping of distribution substations and electrical distribution networks, which are essential aspects of asset management and power system planning. This study aims to analyze and dynamically map substation infrastructure and distribution networks using the MapSource software. The methods used include spatial data collection, data processing using GIS tools, as well as visualization and location-based analysis of distribution networks. The results show that the integration of these two software tools enables real-time monitoring, identification of network vulnerabilities, and optimization of electrical infrastructure development planning. With this approach, stakeholders can make geospatial data-driven decisions to enhance the efficiency and reliability of the electricity distribution system.